Accurate detection of Escherichia coli O157:H7 and Salmonella enterica serovar typhimurium based on the combination of next-generation sequencing and droplet digital PCR. (1st October 2022) - Kong, Jiaqi; Fan, Congcong; Liao, Xiaojun; Chen, Ailiang; Yang, Shuming; Zhao, Liang; Li, Hui
Abstract: Shiga-toxin producing Escherichia coli O157:H7 and Salmonella enterica serovar Typhimurium are important foodborne pathogens which are threatened to human health seriously. In this study, we firstly investigated the application and accuracy of next-generation sequencing (NGS) technology combining with droplet digital PCR (NGS + ddPCR) for the quantification of pathogenic bacteria through amplification of 16S rRNA genes. Absolute quantification by ddPCR was then further developed to identify E. coli O157:H7 and S. Typhimurium targeting the single copy genes Z3276 and invA, respectively . Apple juice, milk and chicken were selected as corresponding represents of fruit, dairy and meat, to investigate the application of ddPCR in different food. The tested microbial communities were all successfully annotated by NGS at the level of species, and the accuracy of absolute abundance calculated by NGS + ddPCR relied on its initial population for each species. When detecting the genes Z3276 and invA simultaneously by dual channels using ddPCR, the detection limit of E. coli O157:H7 and S. Typhimurium in apple juice and milk was 2–3 log cfu/mL, while it was increased to 3–4 log cfu/g on chicken surface. Exist of background species or homologous strains did not affect the accuracy or detection limit of the targeting strain. Highlights: NGS combining with ddPCR for the quantification of pathogenic bacteria. Characterization and quantification of foodborne pathogens at species level. Exist of homologous strains did not affect the accuracy of targeting strain by ddPCR. The detection limit of the targeting pathogens by ddPCR was lower than that of qPCR. E. coli O157:H7 and S. Typhimurium can be quantified in apple juice, milk and chicken.